2020
DOI: 10.3389/fphys.2020.596507
|View full text |Cite
|
Sign up to set email alerts
|

Female Sex Hormone Effects on the Vasculature: Considering the Validity of Restricting Study Inclusion to Low-Hormone Phases

Abstract: Many studies of vascular function limit the testing of premenopausal female participants to periods when female sex hormones, either endogenous or exogenous, are at their lowest concentration. This practice, when not part of the specific research question, may limit data surrounding the predominant physiological state of premenopausal females and pose a threat to external validity. In this Perspective, we briefly review the literature on the effect of female sex hormones on vascular function and discuss when l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 60 publications
0
3
2
Order By: Relevance
“…Also, the small sample size in the HCT group and resulting low power may have contributed to the lack of significant differences in LH, testosterone, estrogen, FMD, and EID, and the results should be interpreted with caution. While previous research has indicated estrogen deprivation is associated with vascular dysfunction,24 estrogen did not differ significantly between groups nor was it associated with any vascular measures. This study did not account for menstrual cycle, although recent studies have shown no changes in endothelial and smooth muscle function throughout menstrual cycle phases in premenopausal women 25.…”
Section: Discussioncontrasting
confidence: 85%
“…Also, the small sample size in the HCT group and resulting low power may have contributed to the lack of significant differences in LH, testosterone, estrogen, FMD, and EID, and the results should be interpreted with caution. While previous research has indicated estrogen deprivation is associated with vascular dysfunction,24 estrogen did not differ significantly between groups nor was it associated with any vascular measures. This study did not account for menstrual cycle, although recent studies have shown no changes in endothelial and smooth muscle function throughout menstrual cycle phases in premenopausal women 25.…”
Section: Discussioncontrasting
confidence: 85%
“…Also, the small sample size in the HCT group and resulting low power may have contributed to the lack of significant differences in LH, testosterone, estrogen, FMD, and EID, and the results should be interpreted with caution. While previous research has indicated estrogen deprivation is associated with vascular dysfunction, 24 estrogen did not differ significantly between groups nor was it associated with any vascular measures. This study did not account for menstrual cycle, although recent studies have shown no changes in endothelial and smooth muscle function throughout menstrual cycle phases in premenopausal women.…”
Section: Discussioncontrasting
confidence: 85%
“…Females provided additional information pertaining to menstrual cycle and hormonal contraception use. Females were not restricted to test during a particular phase of the menstrual cycle as findings pertaining to the effect of menstrual cycle on vascular function in females are limited and equivocal [26]. Furthermore, we did not assess menopausal status and exclude peri-or menopausal women from participating in the study.…”
Section: Experimental Protocolmentioning
confidence: 99%